Uncommon anomalies of the left pulmonary artery during VATS lobectomy for lung cancer. Issue 6 (23rd March 2020) - Amore, Dario; Caterino, Umberto; Casazza, Dino; Imitazione, Pasquale; Saglia, Alessandro; Valentino, Maria Rosaria; Izzo, Alessandro; Curcio, Carlo
Abstract: The key to avoid intraoperative complications due to failure in the preoperative detection of pulmonary vascular anomalies is to perform a careful hilar dissection. Abstract : The key to avoid intraoperative complications due to failure in the preoperative detection of pulmonary vascular anomalies is to perform a careful hilar dissection.